Taxonomic Significance of Petal and Sepal Micromorphological Characteristics in Some Justicia Nees (Acanthaceae) Species in Peninsular Malaysia - Amirul-Aiman Ahmad Juhari,; Noraini Talip,; Che Nurul-Aini Che Amri,; Siti Khaulah Abdul Razak,; Nurul-Syahirah Mansur,; Amalia Rusydi,; Ruzi Abdul Rahman, (Tropical Life Sciences Research, 2019)
Acanthaceae is a flowering plants family under the order Lamiales and comprises at least 4,000 species regardless of tropical and subtropical species with Justicia being the largest genus under this family. The study on the flower’s petal and sepal micromorphology have been done on six Justicia species, namely as Justicia betonica L., J. carnea Lindl., J. comata (L.) Lam., J. gendarussa Burm.f., J. procumbens L. and J. ptychostoma Nees. Methodology used involves fixation, dehydration series, critical point drying technique and observation under scanning electron microscope. Results have shown that all six species have differences in micromorphological characteristics in the sepals and petals epidermal surfaces. Cuticular wax can be found on both abaxial and adaxial epidermal surfaces of petal and sepal for all species studied. Granular cuticular wax is the only type of cuticular wax was found present on petal and sepal of all species studied. There are also eight types of trichomes present on the petal epidermal surface and eight types of trichomes present on the sepal epidermal surface. J. betonica can be recognised directly by having amphidiacytic stomata on petal epidermal surface while stomata were absent on the petal epidermal surface of other species. As a conclusion, findings in this study have proven that petal and sepal micromorphological characteristics have systematic significant and can be used as supporting data for species differentiation and identification in the genus Justicia. Acanthaceae merupakan famili tumbuhan berbunga di bawah order Lamiales dan terdiri daripada sekurang-kurangnya 4,000 spesies di kawasan tropika dan juga kawasan subtropika dengan genus Justicia merupakan genus terbesar. Kajian mikromorfologi petal dan sepal telah dijalankan ke atas ke atas enam spesies iaitu Justicia betonica L., J. carnea Lindl., J. comata (L.) Lam., J. gendarussa Burm.f., J. procumbens L. dan J. ptychostoma Nees. Kaedah kajian termasuklah penetapan bunga di dalam larutan penetap, siri dehidrasi, titik pengeringan genting dan cerapan di bawah mikroskop imbasan elektron. Hasil kajian menunjukkan kesemua enam spesies mempunyai variasi dan perbezaan mikromorfologi pada permukaan epidermis petal dan sepal. Kutikel lilin boleh ditemui pada kedua-dua permukaan epidermis petal dan sepal kesemua spesies yang dikaji. Kutikel lilin butir merupakan satu-satunya jenis kutikel lilin yang ditemui pada kesemua permukaan petal dan sepal spesies kajian. Terdapat lapan jenis trikom ditemui pada permukaan epidermis sepal dan juga lapan jenis trikom pada permukaan epidermis petal. Justicia betonica boleh dibezakan secara langsung dengan kehadiran stomata amfidiasitik pada permukaan epidermis petal dan stomata tidak hadir pada permukaan petal spesies yang lain. Kesimpulannya, hasil kajian ini membuktikan ciri mikromorfologi petal dan sepal mempunyai kesignifikan sistematik dan boleh digunakan sebagai data sokongan bagi pembezaan dan pengenalpastian spesies dalam genus Justicia.